Refleksi Moderasi Beragama: Melangitkan Wahyu Membumikan Fikih - Saeful Bahri (La-Tahzan: Jurnal Pendidikan Islam, 2026)
This study aims to explore the concept of religious moderation through the methodological reflection of "Heightening Revelation and Grounding Fiqh". Current religious challenges are often faced with a dichotomy between static sacred texts and dynamic social realities, triggering the emergence of extreme understandings, both radical-literalist (ifrath) and liberal-permissive (tafrith). Using a qualitative approach, this article argues that religious moderation (wasathiyah) is a crucial methodology to bridge this gap. The concept of "Heightening Revelation" focuses on preserving the transcendental values of the Qur'an and Sunnah as the highest source of ethics and a universal moral compass. Meanwhile, "Grounding Fiqh" is a process of dialectics and contextualization of Islamic law to be adaptive to the changes of the times through the deconstruction of past ijtihad and the reconstruction of human-centric fiqh. The results show that the use of the maqashid as-syariah (objectives of law) framework and the principle of at-taisir (ease) are the main pillars in realizing Islam as rahmatan lil 'alamin.